Observations of Galactic and Extra-galactic Sources From the BOOMERANG and SEST Telescopes - Coble, K.; Ade, P. A. R.; Bock, J. J.; Bond, J. R.; Borrill, J.; Boscaleri, A.; Contaldi, C. R.; Crill, B. P.; de Bernardis, P.; Farese, P.; Ganga, K.; Giacometti, M.; et al. (arXiv, 2003)
We present millimeter-wave observations of three extra-galactic and six Galactic sources in the Southern sky. Observations were made at 90, 150, 240 and 400 GHz with resolutions of 18, 10, 14 and 12 arcmin respectively during the 1998 Antarctic long duration balloon flight of BOOMERANG. Observations were also made with the SEST telescope, at 90 and 150 GHz with resolutions of 57 and 35 arcsec respectively. These observations can be used for calibrations of Cosmic Microwave Background (CMB) experiments as well as an understanding of the physical processes of the sources. : 19 pages, submitted to ApJS